Ancient Cytokine Interleukin 15-Like (IL-15L) Induces a Type 2 Immune Response - Yamaguchi, Takuya; Chang, Chia Jung; Karger, Axel; Keller, Markus; Pfaff, Florian; Wangkahart, Eakapol; Wang, Tiehui; Secombes, Christopher J.; Kimoto, Azusa; Furihata, Mitsuru; Hashimoto, Keiichiro; Fischer, Uwe; et al. (Frontiers in Immunology, 2020)
Related interleukin-2, -15, and -15-like (IL-2, -15, and -15L) are ancient cytokines, with all three genes surviving in extant fish and some mammals. The present study is the first to identify IL-15L functions, namely in rainbow trout. In isolated trout splenocytes, and in vivo, purified recombinant IL-15L+IL-15R molecules induced expression of IL-4 and IL-13 homologues, which are markers of type 2 immunity. In contrast, trout IL-15 stimulated type 1 immune markers, thus IL-15 and IL-15L can have opposing functions. Trout IL-15L was more dependent on “in trans” presentation by the receptor chain IL-15R than IL-15 was, and stimulated CD4-CD8-(IgM-) lymphocytes from thymus and spleen. We propose an important role for IL-15L early in the type 2 immune cytokine cascade. Trout IL-2 and IL-15 exhibited features reminiscent of their mechanistic and functional dichotomy observed in mammals; for example, IL-15 but not IL-2 required a receptor alpha chain (only IL-15R in the case of fish) for its stability, and only IL-15 was efficient in stimulating lymphocytes from mucosal tissues. Data suggest that IL-15L and IL-15 may be particularly effective in stimulating innate lymphocyte type 2 cells (ILC2) and natural killer (NK) cells, respectively, but further identification of the cell types is needed. An interesting finding different from in mammals was the efficient stimulation of CD4+CD8+ thymocytes by IL-2. In short, this study presents fundamental information on the evolution of the IL-2/15/15L cytokine family.